A Case of Prenatally Diagnosed Periventricular Nodular Heterotopia in a Surviving Male Patient with FLNA Mutation - Tencer, Jaclyn; Virupakshaiah, Akash; Campbell, Ian M.; Zackai, Elaine H.; Zarnow, Deborah; Agarwal, Sonika (Journal of Pediatric Neurology, 2021)
FLNA is a gene on the X chromosome that encodes Filamin A, a widely expressed protein crucial for forming the cell cytoskeleton and mediating cell signaling. Loss-of-function mutations have been associated with periventricular nodular heterotopia (PVNH) with associated epilepsy and intellectual deficits, as well as cardiovascular disease, connective tissue disorders, pulmonary disease, bleeding diathesis, and gastrointestinal disease. Alternatively, gain-of-function mutations have been described with otopalatodigital spectrum disorders.The loss-of-function variants of FLNA associated with PVNH have historically been considered lethal in males, often prenatally or by the first year of life. However, more surviving males with FLNA variants are being described. Most of the surviving males have missense or distal truncating mutations or a degree of mosaicism. Others are thought to have splice site mutations or in-frame exon skipping leading to production of some degree of functional Filamin A as possible mechanisms of survival.Here, we presented a case of a 20-month-old small but developmentally appropriate and healthy male infant who was prenatally diagnosed with PVNH, and postnatally found to have a nonsense variant of the FLNA gene. This mutation has not been previously clinically described or published to our knowledge.
Keywords: Filamin A; periventricular nodular heterotopia; FLNA